Optimalisasi Pemasaran Produk Melalui Whatsapp Business Bagi Umkm Pada Kelurahan Gebang Putih - Reksi Daninzia Ramadhanti; Maharani Ikaningtyas (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Society's need for information is increasingly complex, social media can be used as a marketing medium to support business activities and strengthen the function of communication to the public. The lack of knowledge of MSMEs in Gebang Putih Village regarding digital marketing inspired KKN-T students to assist MSMEs in marketing their products through WhatsApp Business. This community service activity is part of the Thematic Real Work Lecture activities which are carried out using training and mentoring methods. The target of this activity is MSME actors in the Gebang Putih Village. Assistance in making Whatsapp Business as an effort to develop and expand digital technology-based marketing networks. With these activities, it is hoped that MSME actors can increase business competitiveness and increase the number of sales so that they can survive in the long term.